Pomen odkrivanja predkliničnih oblik ateroskleroze - Poredoš, Pavel (Zdravniški vestnik, 2006)
Background Atherosclerosis is a chronic disease, which can go on for many decades with no clinically noticable changes. When clinical symptoms appear, the disease has usually already significantly progressed. There is currently no effective treatment for atherosclerosis. The disease can only be prevented.This is why it is important to detect it in its early stages, when preventive measures are the most effective. Today, with a help of non-invasiveinvest tion methods, mostly ultrasound based, we can detect changes in the structure and fu tion of artery wall, which are typical for theearly stages of atherosclerosis or predict disease course. Conclusions Suchchanges are: lower capability of artery expansion during an increased blood flow (endothelial dysfunction), intima-media thickening, artery walls, artery calcination and ankle-brachial index decrease. The research showed thatthese symptoms of preclinical atherosclerosis are tightly connected to authenticity of the risk factors, their number and duration, and that there isa tight connection between the general cardiovascular danger and the manifestation of preclinical and morphological changes of an artery wall. (Abstract truncated at 2000 characters)
Keywords: ateroskleroza; Atherosclerosis; Blood Pressure; Brachial Artery; Brahialna arterija; Calcinosis; Carotid Arteries; Dejavniki tveganja; Diagnosis; diagnostika; Endotelij žilni; Endothelium, Vascular; Kalcinoza; Karotidne arterije; Krvni pritisk; Pathology; Risk Factors; Tunica Intima; Tunica Media; Tunika intima; Tunika medija; Ultrasonography; Vascular Diseases; Žilne bolezni